2020
DOI: 10.7150/thno.50283
|View full text |Cite
|
Sign up to set email alerts
|

Tumor immune profiles noninvasively estimated by FDG PET with deep learning correlate with immunotherapy response in lung adenocarcinoma

Abstract: Rationale: The clinical application of biomarkers reflecting tumor immune microenvironment is hurdled by the invasiveness of obtaining tissues despite its importance in immunotherapy. We developed a deep learning-based biomarker which noninvasively estimates a tumor immune profile with fluorodeoxyglucose positron emission tomography (FDG-PET) in lung adenocarcinoma (LUAD). Methods: A deep learning model to predict cytolytic activity score (CytAct) using semi-automatically seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…To our knowledge, this is the first study to investigate the relationship between SUV max and TMB in patients with diverse cancers. Prior studies have investigated the complex relationship between tumor immune microenvironment and glucose metabolism rate and shown associations between metabolic and immune profiles [ 15 , 16 ]. 2-[ 18 F]FDG PET imaging has been suggested as a diagnostic tool to estimate tumor immune status [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to investigate the relationship between SUV max and TMB in patients with diverse cancers. Prior studies have investigated the complex relationship between tumor immune microenvironment and glucose metabolism rate and shown associations between metabolic and immune profiles [ 15 , 16 ]. 2-[ 18 F]FDG PET imaging has been suggested as a diagnostic tool to estimate tumor immune status [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the rst study to investigate the relationship between SUV max and TMB in patients with diverse cancers. Prior studies have investigated the complex relationship between tumor immune microenvironment and glucose metabolism rate and shown associations between metabolic and immune pro les [15,16]. 2-[ 18 F]FDG PET imaging has been suggested as a diagnostic tool to estimate tumor immune status [17].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated that both PET-based radiomic features provided the prediction of prognostic outcome for lung cancer patients with radiotherapy or chemo-radiotherapy, whereas semiquantitative PET factors were not available [96]. Both PET-based handcrafted and deep features can predict the response of immunotherapy in lung adenocarcinoma [97,98].…”
Section: Applications Of Functional Radiomic Features In Lung Cancermentioning
confidence: 99%